A 43 Years Old Lady with Silent Pheochromocytomaÿa Case Report - Paul, Nandita; Saha, Tarun Kumar; Barman, Tushar Kanti; Das, Anupam; Bhuyian, Rokozzaman; Siddiqua, Sadia Sajmin (Journal of Dhaka Medical College, 2017)
Improvements in imaging studies have resulted in an increase in incidentally discovered adrenal tumors. The adrenal incidentaloma was found in at least 2% on abdominal CT imaging and pheochromocytoma was reported to be about 5.1 to 6.55% among these patients. Here we report a case of silent pheochromocytoma presented as an incidentally discovered adrenal mass on abdominal sonogram. In our case patient had no apparent symptom and sign of pheochromocytoma except mild hypertention . Incidental findings in USG reveal retroperitoneal mass located in right adrenal gland. Finally CT scan of abdomen confirmed adrenal mass. Surgical excision the right adrenal gland was performed with pathological report as a benign pheochromocytoma. Majority of incidentally discovered adrenal masses are non hypersecretory benign adenomas; but a hormone screening evaluation is necessary to reveal cases with clinically unsuspected hypersecretory nature. For prevention of possible lethal outcome, patients with silent pheochromocytoma scheduled to undergo surgery should be treated according to the hemodynamic parameters. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 129-132